2013
DOI: 10.1016/j.jsat.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Possible barriers to enrollment in substance abuse treatment among a diverse sample of Asian Americans and Pacific Islanders: Opinions of treatment clients

Abstract: This mixed methods study examined motivations and barriers to substance abuse treatment entry and treatment continuation among Asian American and Pacific Islander (AAPI) substance users. AAPI substance users (N = 61) were recruited from substance abuse treatment programs in California and Hawaii. Semi-structured interviews and interviewer-administered surveys assessed barriers and facilitators to entering substance abuse treatment. Barriers included peer pressure, family influences, and face loss concerns. Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…As individual SUD clinical trials are too short and small to yield stable estimates, pooling participants across trials creates more stable estimates. Similarities in the CTN participant characteristics population provide a rationale for pooling across trial, such as socioeconomic status, racial and ethnic groups, employment status, and educational level (Calsyn et al, 2009; Campbell et al, 2010; Carroll et al, 2006; Donovan et al, 2013; Hien et al, 2010; Hien et al, 2009; Horigian, Robbins, Dominguez, Ucha, & Rosa, 2010; Korthuis et al, 2012; Kropp et al, 2013; Masson et al, 2013; Meade et al, 2010; Svikis et al, 2012; Weiss et al, 2011; Winhusen, Winstanley, Somoza, & Brigham, 2012; Woody et al, 2008). Participants were typically recruited from community-based substance abuse treatment programs (CTPs) within the CTN network (McCarty et al, 2008) and trials were designed by NIDA CTN investigators with common goals of bridging practice with substance abuse treatment research results (Tai et al, 2010; Wells, Saxon, Calsyn, Jackson, & Donovan, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…As individual SUD clinical trials are too short and small to yield stable estimates, pooling participants across trials creates more stable estimates. Similarities in the CTN participant characteristics population provide a rationale for pooling across trial, such as socioeconomic status, racial and ethnic groups, employment status, and educational level (Calsyn et al, 2009; Campbell et al, 2010; Carroll et al, 2006; Donovan et al, 2013; Hien et al, 2010; Hien et al, 2009; Horigian, Robbins, Dominguez, Ucha, & Rosa, 2010; Korthuis et al, 2012; Kropp et al, 2013; Masson et al, 2013; Meade et al, 2010; Svikis et al, 2012; Weiss et al, 2011; Winhusen, Winstanley, Somoza, & Brigham, 2012; Woody et al, 2008). Participants were typically recruited from community-based substance abuse treatment programs (CTPs) within the CTN network (McCarty et al, 2008) and trials were designed by NIDA CTN investigators with common goals of bridging practice with substance abuse treatment research results (Tai et al, 2010; Wells, Saxon, Calsyn, Jackson, & Donovan, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that there is variability in the way heavy alcohol use is sanctioned (it may be considered acceptable unless overt family problems result), and that alcohol use in some cultures is a normative way of managing stress. Similarly, qualitative interviews with a diverse sample of Asian American clients in treatment for substance use disorders revealed that many respondents recognized the need to address their substance use only when they had experienced significant familial consequences or when they were mandated by the criminal justice system (Masson et al, 2013). Thus, incorporating patients’ cultural and familial contexts in screening and motivating them to reduce substance use is an important adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of studies that have attempted to identify barriers to treatment entry and retention have primarily used qualitative methods and life history interviews to explore the nature of perceived barriers (Jessup et al, 2003;Kenny et al, 2011;Notley et al, 2012;van Olphen, Freudenberg, Fortin, & Galea, 2006;Redko, Rapp, & Carlson, 2006;Richie, 2001;Roberts & Nishimoto, 2006). Some have used interviewer administered surveys, or a self-administered questionnaire along with qualitative interviews (Masson et al, 2013;Venner et al, 2012). Studies which have used quantitative methods have generally involved persons seeking outpatient treatment Rinker et al, 2009;Xu et al, 2007) or those who are not help-seeking but have an identified disorder and would be appropriate for treatment, either because of their history (K. E. Green, 2011;Kenny et al, 2011) or a diagnosed substance use disorder (Mojtabi et al, 2011).…”
Section: Discussionmentioning
confidence: 99%